A digital approach to Tartini’s theoretical works - Umer Kljun, Jerneja (Muzikološki zbornik, 2025)
The article describes the digitisation of Giuseppe Tartini’s manuscripts with the help of hand-written text recognition via the Transkribus app. It explains the basics concepts, describes the training process for a customised model and the tests run on Tartini’s scientific texts. The results of private and public AI models are compared in terms of accuracy, readability and efficiency of the editing process.
Keywords: 18. stoletje; digital humanities; digital musicology; digitalna humanistika; digitalna muzikologija; eighteenth century; HTR; Tartini, Giuseppe; Transkribus